Normative Data of the Wingate Anaerobic Test in 1 Year Age Groups of Male Soccer Players - Nikolaidis, Pantelis Theodoros; Matos, Bruno; Clemente, Filipe Manuel; Bezerra, Pedro; Camões, Miguel; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
The Wingate anaerobic test (WAnT) has been used extensively to evaluate performance in soccer; however, a comprehensive sport-specific normative database has not been available so far. Therefore, the main aim of the present study was to develop norms of the main indices of the WAnT with regards to age in soccer. A secondary aim was to examine the relationship of WAnT with two common field tests, 20m sprint and vertical jump, and study the variation of this relationship by age and playing position. 995 male soccer players (age 18.1±4.9 years) performed the WAnT, and a sub-sample of 190 soccer players (age 19.4±5.1 years) performed 20m sprint, squat (SJ) and countermovement jump (CMJ). Age was related very largely with peak power (R2=0.57) and mean power of the WAnT (R2=0.60) when they were expressed in W, and largely (R2=0.41 and R2=0.33, respectively) when they were expressed in W.kg-1, whereas it did not relate with fatigue index. After being adjusted for age, a relationship of SJ (B = 3.91, 90% CI: 2.49, 5.32; ; R2=0.26), CMJ (B = 3.59 , 90% CI: 2.22, 4.95; ; R2=0.24) and 20m sprint (B = -0.06, 90% CI: -0.10; -0.01; R2=0.19) with peak power of the WanT was observed. In summary, Ppeak and Pmean were related very largely to age, especially during adolescence, and percentile norms of these indices were developed for 1-year age groups from 11 to 21 years old and for a single adult age group (22-39 years old). These findings on the largest dataset of soccer players ever studied would be expected to offer a practical tool to the members of the sports medicine team (e.g. exercise physiologists, fitness trainers, and coaches) working with them.